Pemanfaatan Narrowband IoT (NB-IoT) dalam Peningkatan Produktivitas Peternakan melalui Monitoring Otomatis - Rakhman, Arif; Sutanto, Achmad; Hernowo, Rudi (Politeknik Harapan Bersama, 2023)
The rapid advancements in Narrowband IoT (NB-IoT) technology present significant opportunities for creating innovative products that can be implemented in daily life. One of these innovative products is the utilization of NB-IoT for monitoring cage conditions, maintenance, and boosting livestock productivity under challenging conditions that are difficult to manually control. This study aims to design an automated system capable of maintaining ideal cage conditions, including temperature, humidity, levels of ammonia (NH3 and CO2), as well as providing feed/water to livestock automatically and periodically. The research methodology involves the integration of various sensors mounted on a microcontroller, such as temperature sensors, humidity sensors, ammonia sensors, water level sensors, and pH sensors. The program executed by this microcontroller is connected to a control panel, and through the internet network, control and monitoring can be carried out using mobile and desktop devices. The test results indicate that this system is capable of providing ease in controlling the chicken coop for owners and workers, maintaining poultry health, and increasing livestock product yields from 97.17% of harvested poultry to 98.263%, with a decrease in the mortality rate from 2.830% to 1.737%. Overall, the utilization of NB-IoT technology in this research provides a positive impact on livestock management, offering an automated solution that enhances efficiency and productivity in the agricultural sector.